Pengaruh Kepemilikan Institusional, Ukuran Perusahaan, dan Leverage terhadap Return Saham - Erselia Trinisa; Efrizal Syofyan (Universitas Negeri Padang, 2024)
This study aims to determine the effect of institutional ownership, firm size, and leverage on stock returns. This research was conducted on 15 agricultural sector companies listed on the Indonesian Stock Exchange, with the period of the research during 5 years (2018-2022). This study uses secondary data obtained by using data collection technique in the form of annual report documents. The sampling technique for this research uses a purposive sampling technique. The analytical method using SPPS (Statistical Product and Service Solution) version 25. The results show that leverage has a negative and significant effect on stock returns, while institutional ownership and firm size have no effect on stock returns.